Enabling Engineering Performance Skills: A Program to Teach Communication, Leadership, and Teamwork - Seat, Elaine; Parsons, J. Roger; Poppen, William A. (Journal of engineering education (Washington, D.C.), 2001)
A minor in Engineering Communication and Performance is being created at the University of Tennessee in conjunction with the engage Freshman Engineering Program. This minor provides engineering undergraduate students with formal training and a credential in complementary performance skills necessary for success in today's workplace. This interdisciplinary program is designed to improve the ability of engineering graduates to work on teams, to be effective communicators, to be socially adept, and to be prepared for leadership roles. Five courses compose the minor. Three of these courses are new and custom‐prepared for engineering students, while the other two may be selected from a limited list of courses that provide in‐depth training on supervision, cultural diversity, and interpersonal interaction. This multi‐disciplinary program takes a novel approach in the subject matter presentation and in the method of coaching students to use these skills. In the custom courses, students receive instruction and are placed in mini‐practicums. To complete the minor, students participate in a full practicum in a social service setting. This paper discusses assessment; course development; program basis and development; strategies for implementation of this new program; integration between engineering, counseling psychology, and human services; and student, faculty, and industry response to the program. The collaboration makes this program transportable to other institutions as it is dependent on having institution expertise in the disciplines of counseling and human services rather than having engineering educators with expertise in these fields. Our experience with establishing this collaboration will also be discussed.